Economic Efficacy: Exploring Decision-Making In Islamic School Budgeting For Enhanced Resource Allocation - Teguh Trianung Djoko Susanto; Sri Maryati; Adi Wulandari; Stevanni Reynita Goentomo; Andita Putri Ramadhania (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Making the right decisions in determining Islamic School budgets is a key element to secure the efficiency and sustainability of the education system. The purpose of this study is Economic Efficacy: Exploring Decision-Making in Islamic School Budgeting for Enhanced Resource Allocation. This research method is based on a qualitative approach that allows researchers to understand in depth the context of decision making in Islamic School budgeting. The results of this study show that decision making in Islamic School budgeting plays a key role in the economic effectiveness of education resource allocation. Several key findings highlight the complexity and variety of factors influencing the decision-making process, including education priorities, government policies, and pressure from stakeholders. The results of this study show that Data analysis and the use of accurate information have proven essential in ensuring effective decision making. Islamic Schools that use solid data to evaluate student performance and the effectiveness of educational programs tend to make better decisions in budget allocation